The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/iej.13233
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of randomized clinical trials comparing rotary canal instrumentation techniques with manual instrumentation techniques in primary teeth

Abstract: Background Use of rotary instruments in the root canals of permanent teeth is well known; however, there are no evidence‐based recommendations on the effectiveness of rotary canal instrumentation techniques over manual instrumentation techniques during root canal treatment in primary teeth. Aim To appraise the current literature on the effectiveness of rotary canal preparation techniques compared to manual techniques during root canal treatment in primary teeth. Data sources MEDLINE, Embase, Cochrane Library, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 30 publications
(98 reference statements)
4
35
1
3
Order By: Relevance
“…Therefore, the chance of subjective bias toward rotary instrumentation with regard to instrumentation time cannot be excluded as the assessment of outcome is not objective (Figure 2). The present review results contradict the observations of the previous systematic review 30 where the low risk of bias was ascertained to the bias in the measurement of outcome. The variation in the observations might be because the present review primarily focuses on the observation of instrumentation time in the included trials and the risk of bias was also assessed for the same.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, the chance of subjective bias toward rotary instrumentation with regard to instrumentation time cannot be excluded as the assessment of outcome is not objective (Figure 2). The present review results contradict the observations of the previous systematic review 30 where the low risk of bias was ascertained to the bias in the measurement of outcome. The variation in the observations might be because the present review primarily focuses on the observation of instrumentation time in the included trials and the risk of bias was also assessed for the same.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, except for one trial, 20 none of the included trials have mentioned regarding the allocation concealment in the trial, which shows 'some concerns' in domain 1 of the RoB 2 tool. Similar findings were observed in the previously reported systematic review 30 where similar concerns were observed in the randomization procedure.…”
Section: Comparisons Of Studiessupporting
confidence: 91%
“…In the study by Pasqualini et al, the manual glide path procedure probably increased analgesic consumption compared with the continuous rotary glide path procedure by extruding more contaminated debris into the periapex [17,18]. Pulpal and periodontal diagnoses, pre-operative pain and intraoperative factors such as irrigation solution and system, instrumentation technique, use and type of medicament, root canal filling technique and occlusal reduction have been previously shown to influence post-operative pain and could justify differences between study results [3,[69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…No intervalo de 24, 48 e 72 horas não foi observada nenhuma diferença significativa entre os grupos de instrumentação com limas rotativas e manual. Resultados semelhantes foram observados porManchanda et al 2020, no entanto, no estudo realizado não foi possível concluir que a limpeza do sistema de canais radiculares é mais eficiente quando comparada a instrumentação manual.Os instrumentos rotatórios modelam melhor o canal radicular, no entanto, este ponto pode não ser relevante para dentes decíduos, uma vez que os canais são mais delgados e precisamos ter mais cuidado ao realizar o desgaste. No entanto paraPrabhakar et al 2016, os instrumentos rotatórios reduzem o tempo de trabalho, sendo este o mais adequado para o tratamento de dentes decíduos, pois aumenta a cooperação da criança durante o procedimento endodôntico.…”
unclassified